Plano nacional de qualificação: limites e dificuldades do PlanTeQ - Rossetti, Maria José (2012)
This study aims to investigate how public policy qualification is structured in the State of Paraná, and the challenges imposed by the rules established by the Ministry of Labour and Employment (MTE), which are presented for the operationalization and implementation of the Territorial Plan Qualification (PlanTeQ), part of the National qualification (PNQ), qualification plan created by the president Lula in 2003, which have their management in the Ministry of Labour Employment (MTE), which uses funds from the Fund for Workers (FAT) for the execution of actions qualifying. Conceptual study will be presented about qualification, the origins of public policies on labor, employment and income, origins, concepts principles and procedures of the National Qualification will be discussed and finally the implementation of PlanTeQ/2010, showing difficulties and limits on its operation. Finally, will be presented considerations about the limits, the difficulties in implementing the PlanTeQ/2010 and suggestion operationalization of public policy for social and professional qualification.